Partisipasi Dan Keaktifan Berdiskusi Peserta Didik Dalam Pembelajaran Biologi Kelas VIII SMP Negeri Oenenu - Dau, Maria Irma Dau; Kristanti, E.; Shidik, Muhammad Amran (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2024)
This research was conducted with the aim of finding out students' participation and active discussion in biology learning in class VIII of Oenenu State Middle School. The population in this study were all class VIII students at Oenenu State Middle School for the 2022-2023 academic year and the research sample was 20 students consisting of one class, namely class VIIIA. This research uses quantitative descriptive methods. The data collection technique used in this research was filling out an observation sheet with 12 questions. Based on data from research conducted at Oenenu State Middle School, it shows that there is student participation and active discussion. On the indicator of student participation, respondents' answers had an average value of 73.33%, while on the indicator of student activity, respondents' answers had an average value of 75.62%. Based on the results obtained from the overall indicators of participation and activeness, class VIII students at Oenenu State Middle School received a good category. Key words: Participation, active discussion of students in biology learning.